Evaluation of Tax Management Related to the Implementation of Effective Rate Income Tax 21 at PT XYZ - Pertiwi, Hanna; Anggraita, Viska (Quantitative Economics and Management Studies, 2024)
The application of effective rates of Income Tax 21 has the potential to cause excess tax payments, this is because Income Tax 21 that has been deducted in each tax period throughout the tax year will be recalculated at the end of the year using progressive rates. This study aims to evaluate the application of tax management in the implementation of the imposition of effective rates of Income Tax 21 related to the implementation of obligations and rights to Income Tax at PT XYZ as a BUMN company. The method in this study is qualitative with a study approach and using triangulation. The results of this study indicate that PT XYZ has implemented tax management for the implementation of its obligations and rights to the implementation of effective rates of Income Tax 21 well. However, PT XYZ can improve the efficiency and effectiveness of the stages of implementation and control of tax management.